BOOK REVIEW: Mircea Dumitru, Cristian Iftode, Savu Totu (eds.), “2400 Years of Thinking with Aristotle”, Editura Universității din București, București, 2020 - Radu SIMION (Studia Universitatis Babeș-Bolyai. Philosophia)
Published in 2020 at Editura Universității din București (University of Bucharest Publishing House), the book “2400 Years of Thinking with Aristotle” gathers together the contributions of participants at the International Conference 2400 Aristotle, hosted by Faculty of Philosophy at the University of Bucharest in 2016, celebrating “Aristotle Anniversary Year”, announced by UNESCO. This volume represents a generous contribution to the western philosophical cultural, its horizon opening opportunities for a more precisely form of Stagirite’s discourse, covering theories and concepts of political philosophy, ontology, logic, ethics, aesthetics, anthropology and cosmology.